Vpliv vibriranja med varjenjem in po njem na mehanske lastnosti zvarov, zavarjenih v zaščiti močno ioniziranega večkomponentnega plina - Pučko, Bogdan (Strojniški vestnik, 2000)
The vibrational stress relief (VSR) technique has been shown to reduce the internal residual stress coused by welding. By lowering or redistributing the stress it is possible to alter the mechanical properties of the weld joint. The aim of this study was to determine the effect of vibration on the properties of multilayer weld specimens which were welded and vibrated under various conditions. Specimens which were stress annealed, vibrated after and during welding were compared with specimen in the as-welded condition. Each specimen was welded using the T.I.M.E. (transfered ionized molten energy) process.
Keywords: VSR; vibriranje; odprava napetosti; postopek TIME; obločno varjenje; mehanske lastnosti; zvari